Late-Gestation in utero Heat Stress Limits Dairy Heifer Early-Life Growth and Organ Development - Dado-Senn, Bethany; Field, Sena L.; Davidson, Brittney D.; Casarotto, Leticia T.; Marrero, Marcela G.; Ouellet, Veronique; Cunha, Federico; Sacher, Melissa A.; Rice, Cash L.; Maunsell, Fiona P.; Dahl, Geoffrey E.; Laporta, Jimena (Frontiers in Animal Science, 2021)
Dairy calves exposed to late-gestation heat stress weigh less, have impaired immunity, produce less milk across multiple lactations, and have reduced productive life. However, less is known about the relationship between in utero heat stress and organ morphology and development. Herein, we characterized the consequences of late-gestation in utero heat stress on body and organ growth trajectories during early-life development. Holstein heifers were either in utero heat-stressed (IU-HT, n = 36, dams exposed to THI > 68) or cooled (IU-CL, n = 37, dams exposed to THI > 68 with access to active cooling) during late gestation (54 ± 5 d prepartum). All heifers were reared identically from birth to weaning. Upon birth, calves were weighed and fed 3.78 L of colostrum followed by 0.87 kg DM/d milk replacer (MR) over two feedings and ad libitum starter concentrate daily. Weaning began at 49 d and ended at 56 d of age. Feed intake was recorded daily, and body weight (BW) and other growth measures were recorded at 0, 28, 56, and 63 d. Blood was collected at d 1 then weekly. Subsets of heifers were selected for euthanasia at birth and 7 d after complete weaning (n = 8 per group each) to harvest and weigh major organs. Reduced BW and stature measures persisted in IU-HT heifers from 0 to 63 d of age with a 7% lower average daily gain and reduced starter consumption relative to IU-CL heifers. IU-HT heifers had lower hematocrit percentages and reduced apparent efficiency of absorption of IgG relative to IU-CL heifers. Additionally, IU-HT heifers had reduced gross thymus, spleen, thyroid gland, and heart weight at birth and larger adrenal glands and kidneys but smaller ovaries relative to BW at 63 d. The mammary gland of IU-HT heifers was smaller relative to IU-CL heifers at birth and 63 d adjusted for BW, suggesting mechanisms leading to impaired milk yield in mature IU-HT cows are initiated early in development. In summary, in utero heat stress reduces whole-body size and limits development of key organs with potential repercussions on dairy calf metabolic adaptation, immune function, and future productivity.